1983
DOI: 10.1093/hsw/8.1.57
|View full text |Cite
|
Sign up to set email alerts
|

A psychosocial Assessment Framework for Cancer Patients and their Families

Abstract: This article describes four areas of knowledge for social work assessments that cover the ecological system of the patient and psychodynamics. In addition, it addresses the area of dis-synchrony, which causes stress for many patients. The author focuses on the area of dis-synchrony because she believes that social workers must be clear about the differences between reactions of pathological patients and strong reactions of psychologically normal patients to extraordinary circumstances. The literature on stress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

1986
1986
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…Additional stressors at the time of diagnosis include difficulties in processing medical information and being able to provide an age-appropriate explanation of this information to the child, managing one's own emotional reaction to the diagnosis, reorganizing family routines to accommodate the demands of treatment, and redefinition of role functions. 48,49 A study conducted by Freeman et al 50 identifying the most predominant stressors at each phase of treatment found communication of prognosis and concerns about the cause of the brain tumor to be the most prevalent stressors at the time of diagnosis.…”
Section: Stressors Specific To Parents Of Children With Cancermentioning
confidence: 99%
“…Additional stressors at the time of diagnosis include difficulties in processing medical information and being able to provide an age-appropriate explanation of this information to the child, managing one's own emotional reaction to the diagnosis, reorganizing family routines to accommodate the demands of treatment, and redefinition of role functions. 48,49 A study conducted by Freeman et al 50 identifying the most predominant stressors at each phase of treatment found communication of prognosis and concerns about the cause of the brain tumor to be the most prevalent stressors at the time of diagnosis.…”
Section: Stressors Specific To Parents Of Children With Cancermentioning
confidence: 99%
“…For example, the developmental stage of the family experiencing breast cancer often includes middle-aged primary caregivers who are balancing multiple responsibilities to the patient, other family members, and themselves. Christ (1983) identified predominant transition points in the cancer experience as diagnosis, treatment initiation, treatment completion, cure, treatment failure, recurrence, decision to discontinue treatment, terminal illness, and death. Although no such clear demarcations exist for related transitional emotional stages (Lewis, 1993), family members may respond to cancer with concerns that vary with the time since diagnosis, disease status, and the patient's condition (Woods, Lewis, & Ellison, 1989).…”
Section: Literature Review Family Cancer Experiencementioning
confidence: 99%
“…According to the treatment results, we may refer to ‘orphaned families and their psychological problems’ or the ‘survivors who need to live with the ghost of cancer’ both in terms of the possible return of the disease or its genetic burden. Christ [ 2 ] identified main transition points for the patient and the family, being: diagnosis, treatment initiation, treatment completion, cure, treatment recurrence, decision to discontinue treatment, terminal illness and death. All of these may be a source of intense stress and concern and may bring about the destabilisation of family life.…”
Section: Introductionmentioning
confidence: 99%